(untitled) (Research, Society and Development, 2021)
In the 2021 school year, the Department of Education provided teachers from the state public schools of Mato Grosso with the Google Classroom tool. It is a resource for the educator to conduct interactive virtual classes and facilitate learning. We asked if, in the state of Mato Grosso, the teacher would be prepared to use this resource. Thus, the objective of this article is to study and describe this tool, through bibliographic and descriptive methodology based on theorists: Bakhtin (2003), Bronckart (2007), Chiapinotto (2010), Moran (1999) and Vigotsky (2005). It is expected to publicize the possibility of associatiating the analog teacher with the technological one through the Google Classroom feature.